MANIFEST MANIFESTATIONS OF ACUTE LEUKEMIA. CLINICAL CASE - Ніколаєнко-Камишова, Тетяна; Чумак, Володимир; Власенко, Анатолій (SWorldJournal, 2025)
The clinical case of polysyndromic manifestation of acute leukemia with rapid development of severe complications that led to death is considered. The progressive deterioration of the patient's condition was caused by fever, rapid lymph node enlargement,